Manipulating the Optical Properties of Carbon Dots by Fine‐Tuning their Structural Features. Issue 19 (10th September 2019) - Luo, Hui; Papaioannou, Nikolaos; Salvadori, Enrico; Roessler, Maxie M.; Ploenes, Gereon; van Eck, Ernst R. H.; Tanase, Liviu C.; Feng, Jingyu; Sun, Yiwei; Yang, Yan; Danaie, Mohsen; Belen Jorge, Ana; et al.
Abstract: As a new class of sustainable carbon material, "carbon dots" is an umbrella term covering many types of materials. Herein, a broad range of techniques was used to develop the understanding of hydrothermally synthesized carbon dots, and it is shown how fine‐tuning the structural features by simple reduction/oxidation reactions can drastically affect their excited‐state properties. Structural and spectroscopic studies found that photoluminescence originates from direct excitation of localized fluorophores involving oxygen functional groups, whereas excitation at graphene‐like features leads to ultrafast phonon‐assisted relaxation and largely quenches the fluorescent quantum yields. This is arguably the first study to identify the dynamics of photoluminescence including Stokes shift and allow the relaxation pathways in these carbon dots to be fully resolved. This comprehensive investigation sheds light on how understanding the excited‐state relaxation processes in different carbon structures is crucial for tuning the optical properties for any potential commercial applications. Abstract : Dot products : The structural evolution of hydrothermally synthesized carbon dots after oxidation and reduction is studied, and it is demonstrated how fine‐tuning of the structure can dramatically change their optical properties. An in‐depth spectroscopic analysis identifies the dynamics of photoluminescence, and this allows the relaxation pathways in these carbon dots to be fully resolved.